2007
DOI: 10.1111/j.1524-4733.2007.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Stem Cell Transplantations from Unrelated Donors in Adult Patients with Acute Leukemia

Abstract: Although both types of stem cell transplantations are associated with a high short-term mortality and high cost, the cumulative gains in life-years of survivors can be substantial, resulting in ICERs compared with no transplantation that are usually considered acceptable. However there is less certainty about this conclusion with cord blood transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 45 publications
1
38
0
3
Order By: Relevance
“…In another study, conducted by Esperou et al in 2004 on 85 patients from five transplant centers, the mean cost for the first 6 months after transplantation, restricted to a specific protocol, was € 76,000. 35 The average cost for initial hospitalization for UCBT in Canada 22 and in the USA 21 was consistent with that in our series. However in both studies, only costs up to 100 days were included whereas in other studies costs were considered over a much longer period.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In another study, conducted by Esperou et al in 2004 on 85 patients from five transplant centers, the mean cost for the first 6 months after transplantation, restricted to a specific protocol, was € 76,000. 35 The average cost for initial hospitalization for UCBT in Canada 22 and in the USA 21 was consistent with that in our series. However in both studies, only costs up to 100 days were included whereas in other studies costs were considered over a much longer period.…”
Section: Discussionsupporting
confidence: 77%
“…21,22 The acquisition cost of two cord blood units is one of the main limitations of using dUCBT. The median cost for the first 100 days after UCBT was estimated to be around US$ 80,407 in Canada in 2007 22 and around US$ 137,564 in the USA in 2009, 21 not including the cost for the donor search. In a more recent study from the Erasmus University, 23 the cost of UCBT over 1 year was estimated to be around € 250,000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pragmatic search using Google and Google Scholar found two papers deemed relevant to the primary aim of the review. 182,183 Costa et al 182 conducted a cost-effectiveness evaluation of unrelated stem cell transplantation for adults with acute leukaemia (ALL and acute myeloid leukaemia) structured around a 20-year Markov model. The study concluded that the two forms of transplantation considered (cord blood and bone marrow/peripheral blood stem cells) were cost-effective compared with no transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…The 'cure point' was assumed to represent the time at which patients are assumed to no longer be at risk of disease relapse. The study by Costa et al 182 assumed that at 5 years post transplantation the patient will be free of any procedural mortality…”
Section: Implications For Model Conceptualisationmentioning
confidence: 99%